Pharmacological Studies And Establishment Of Tissue Culture For Hymenocallis Litoralis - Sundarasekar, Jeevandran (2012)
Hymenocallis littoralis an ornamental plant exhibits numerous therapeutic properties such as anti-Candida, antioxidant, cytotoxicity and wound healing activities. Hymenocallis littoralis parts including anther, bulb, flower, leaves, stem and roots were extracted via sonication technique using methanol solvent. The wild plant extracts was subjected to anti-Candida activity and it shows promising activity against Candida albicans strain (ATCC 10231). The flower and root methanolic extracts exhibits better anti-Candida activity at 6.25 mg/mL as minimum inhibitory concentration (MIC). Scanning and transmission electron microscopy analysis reveals the cells lost its cell wall contact integrity and also nucleus properties at 36 h of treatment.